Monitoring modifiable injury risk factors over an in-season mesocycle in semi-professional female field hockey players - Sánchez-Migallón, V.; Moreno-Pérez, V.; Terrón-Manrique, P.; Fernández-Ruiz, V.; Blake, C.; Navandar, A.; López Samanes, Á. (BMC Sports Science, Medicine and Rehabilitation, 2024)
Objective This study aimed to determine changes of modifiable injury risk factors and fatigue parameters during a mesocycle (4 months of the competitive season) in semi-professional female field hockey players (Spanish 2nd Division).